2005
DOI: 10.1002/art.20869
|View full text |Cite
|
Sign up to set email alerts
|

Anti–ribosomal P protein antibody in human systemic lupus erythematosus up‐regulates the expression of proinflammatory cytokines by human peripheral blood monocytes

Abstract: Objective. Autoantibodies to ribosomal P proteins (anti-P antibodies) are detected in 12-16% of patients with systemic lupus erythematosus (SLE) and have been found to be associated with some manifestations of the disease, including lupus psychosis and hepatitis. Recent studies have disclosed that anti-P antibodies react with activated T cells but not with B cells, suggesting possible direct effects of anti-P antibodies on immune regulation. The present study was designed to explore the presence of the epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 14 publications
3
43
0
1
Order By: Relevance
“…Previous studies have determined that artificial histone acetylation at the TNFα locus is sufficient to increase the cells ability to respond to stimuli but does not lead in and of itself to transcription of TNFα [20]. Thus, we would hypothesize that the high serum levels of TNFα that are seen in SLE patients are due both to an increased competence to produce TNFα and to the presence of a stimulus, either or both of which may be a consequence of the disease process [43]. The immunology of SLE is extremely complex and there is evidence that histone acetylation at certain genetic loci may correlate with biochemical or phenotypic disease features while acetylation of other loci appears to be protective [35;44].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have determined that artificial histone acetylation at the TNFα locus is sufficient to increase the cells ability to respond to stimuli but does not lead in and of itself to transcription of TNFα [20]. Thus, we would hypothesize that the high serum levels of TNFα that are seen in SLE patients are due both to an increased competence to produce TNFα and to the presence of a stimulus, either or both of which may be a consequence of the disease process [43]. The immunology of SLE is extremely complex and there is evidence that histone acetylation at certain genetic loci may correlate with biochemical or phenotypic disease features while acetylation of other loci appears to be protective [35;44].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, anti-ribosomal P (anti-P) antibodies in the serum have been shown to be associated with diffuse NPSLE (4,16,19). We have recently demonstrated that anti-P antibodies up-regulate the expression of tumor necrosis factor ␣ protein and messenger RNA in human peripheral blood monocytes (20). Since tumor necrosis factor ␣ has been found to abrogate the integrity of the blood-brain barrier (21,22), it is likely that serum anti-P antibodies might also induce blood-brain barrier impairment and thus allow anti-NR2 in the systemic circulation to enter the CNS, leading to the development of neuronal damage.…”
Section: Discussionmentioning
confidence: 98%
“…As for the mechanism explaining this causal relationship, antiribosomal P positive sera from SLE patients were found to react strongly "in vitro" with a polypeptide antigenically related to a 38 kD ribosomal P0 protein present on the plasma membrane of hepatoma cells [28] , thus further strengthening the possibility that anti-ribosomal P antibodies could be directly detrimental in lupus patients by inducing hepatocellular lysis, and further transaminase release. Finally, anti-ribosomal P antibodies up-regulate the expression of proinflammatory cytokines by peripheral monocytes in SLE, which may be a contributing factor for hepatitis development [29] . Given that auto-antibodies directed against eukaryotic P proteins are highly specific to SLE, they can be used as diagnostic markers of the disease.…”
Section: Lupus Hepatitismentioning
confidence: 99%